Chemical Composition, Antioxidant Activity, and Multivariate Analysis of Four Moroccan Essential Oils: Mentha piperita, Mentha pulegium, Thymus serpyllum, and Thymus zygis - Mohamed Amine El Maimouni; Soukaina El Amrani; Mouhcine Fadil; Naoual Menyiy; Rabia Bouslamti; Saoussan Annemer; Sanae Lairini; Abdelhakim El Ouali Lalami (The Scientific World Journal)
Conclusion: The EOs derived from M. piperita, M. pulegium, T. serpyllum, and T. zygis species might be exploited as a natural source for antioxidant activity.